Hybrid open and endovascular repair of a blunt traumatic thoracic aortic injury in a 7 year old boy - Jennifer M. Brewer; Sarah Grout; Mohiuddin Cheema; Thomas Divinagracia; Carissa Webster-Lake; Douglas Moote; Nahum I. Kryzman; Edward Cortland; Brendan T. Campbell (Elsevier, 2019)
We describe a 7-year-old boy who sustained a blunt thoracic aortic injury following a rollover motor vehicle crash where the vehicle fell 200 feet down an embankment. The chest x-ray on arrival showed widening of the superior mediastinum, a left-sided hemothorax, and first rib fracture. The screening CTA of the chest revealed bilateral pulmonary contusions, a large left hemothorax, and evidence of aortic injury with active contrast extravasation. The patient was intubated due to respiratory distress and had a left chest tube placed. The patient became hypotensive with greater than 1.5 L of blood from the chest tube, so a resuscitative thoracotomy was performed. Bleeding was controlled with a sponge stick initially and definitively with a Satinsky vascular clamp. Next the patient was transported to the hybrid OR at the adjacent adult hospital with an open chest for endovascular graft placement. The patient was admitted to the PICU post-operatively, transferred to the floor on POD 4, and discharged home on POD 9. Aortic injury after blunt trauma in pre-adolescent children is uncommon and often fatal. Endovascular repair of traumatic thoracic aortic injury in adults is currently the standard of care, but there is a paucity of clinical data to guide management of these types of injuries in pediatric patients.